Feeding of Pseudocalanus minutus on living and non-living particles. - Poulet, S.A. (Marine Biology, Berlin, 1976)
A seasonal study of carbon content of living and of carbon and nitrogen content of non-living particulate material in seawater is presented. Grazing by Pseudocalanus minutus on living and non-living particles has been investigated over 1 year. Seasonal variations in the food uptake were associated with seasonal variations of each chemical component of the particles in the water. The amount of non-living carbon constituted the major part of the food ingested, irrespective of season. The ingested living carbon always accounted for a small fraction of the total copepod body carbon. The proportion of living carbon ingested could be equivalent to or even higher than non-living carbon at times during the late spring, summer and fall. The concentration of both living and non-living material within each particle peak of the spectra in the water seemed to affect the balance between non-living and living particle uptake. Non-living particles cannot be considered only as a supplementary food source for small copepods; they are a basic food for P. minutus at all times.